Missile injuries to the external genitalia: a five year experience in Maiduguri, North Eastern Nigeria - Dogo, Hassan Mohammed; Ibrahim, Ahmed Gaddams; Gana, Yakubu Lawan (International Journal of Research in Medical Sciences, 2017)
Background: There is a tremendous increase in violence as a result of the insurgency that is currently afflicting our region. Injuries from Gunshot and improvised explosive devices (IEDS) are quite common and the external genitalia is longer exempted from such injuries. Methods: The study reviewed all patients with missile injuries to the external genitalia managed in the University of Maiduguri Teaching Hospital (U.M.T.H) between January 2011 and December 2015. Results: A total of 51 patients had injuries to the external genitalia. Seven were excluded for incomplete data and 44 patients were analyzed. Age ranged from 5-70 years with a mean of 32.75 years and a male to female ratio of 10:1. The peak age group was 30-39 years accounting for 31.82%. The injuries were scrotal 65.91%, and penis 20.45%. Procedures done were wound debridement in all patients, and delayed primary closure in 43.18%. The outcome was satisfactory in terms of cosmesis, erectile and voiding functions. Conclusions: Genital missile injuries are on the increase with militarization of civilian population. Goals of treatment still remain cosmesis, preservation of erectile and voiding function.